Genotype–environment interactions and inheritance of quantitative traits in a hybrid combination between seeded and seedless grapevine cultivars (Vitis vinifera L.) - V. Roychev (Труды по прикладной ботанике, генетике и селекции)
The genotype–environment interactions and the inheritance of quantitative traits in a hybrid combination between a seeded grapevine cultivar and a seedless one (Armira × Rusalka 1) have been studied. It has been found that the selection of valuable hybrid forms shall become more efficient when conducted according to the traits ‘flowering – berry softening’, ‘berry softening – technological maturity’, ‘cluster weight’, ‘weight of 100 berries’ and ‘acids’. Dominant gene interactions with the environment are characterized by significantly greater intensity in comparison to those of additive genes. Inheritance in F1 progeny manifests very high values for the traits ‘budding’, ‘flowering’, ‘budding – flowering’, ‘flowering – berry softening’, ‘berry softening – technological maturity’, ‘berry length’. ‘berry width’, ‘weight of 100 berries’, ‘sugars’ and ‘acids’. According to the genetic stability of the dominant parameter interacting with the environment, a comparative evaluation can be made for each trait and, depending on the selection purpose, elite hybrid plants can be singled out, which possess a combination of the most important commercial traits.